Effects on Children’s Health by Excessive Use of Online Devices: A Study from the Parents Perspectives - Palikhe, Amin; Adhikari, Nabin Bahadur (Journal of Nepalese Business Studies, 2021)
This paper aims to identify the patterns of excessive use of online devices by children and its physical and behavioural impact on children's health of five different age groups: 0- less than 3, 3-7, 7-10, 10- 13 and over 13years of age. A survey was conducted with 42 respondents by using an on-line Google form in Pokhara. The purposive sampling method was used to select the sample and an online questionnaire was used to accumulate data from the parents. The target sample groups are parents who have children with age below 14 years. It is not a surprising matter that children have become good operators of any online devices these days. Therefore, this research paper attempts to find out any relationships that exist between online device user children and physical problems that they suffer. So a hypothesis has been developed to test whether “excessive online devices uses affects children’s health?” A hypothesis was tested through Kendall's tau-b (τb) correlation coefficient, a non-parametric test. This paper concludes that the time is managed by the parent to their children for the use of the internet. Due to this effort of the parents, there is no serious physical health problem arising in the children and the parents are also not worried about their excessive engagement on electronic gadgets.